The Effect of Interest Rate, Inflation and Exchange Value on Stock Returns with Profitability as Intervening Variables - Nevi Kusumaningtyas; Bambang Widagdo; Dewi Nurjannah (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
The purpose of this study is to prove interest rates, inflation, and exchange rates that affect stock returns with profitability as an intervening variable in the banking sector listed on the Indonesia Stock Exchange. The research method used purposive sampling, considering the consideration of taking the sample of financial reports published in 2015-2019 with a total of 12 banking companies. The research method uses Partial Least Square to prove the effect of exogenous variables on endogenous variables by using intervening variables. The test results show that interest rates and inflation have a positive effect on profitability. the exchange rate has a negative effect on profitability. Interest rates, inflation, and exchange rates have a negative effect on stock returns, while profitability has a positive effect on stock returns. Profitability is unable to intervene in the effect of interest rates, inflation and exchange rates on stock returns